Zwei Erzählungen regionaler Entwicklung in Süddeutschland: vom Sektorenmodell zum Produktionssystem = Two narratives of regional development in Southern Germany : from the three-sector model to the production system - Glückler, Johannes; Punstein, Anna Mateja; Wuttke, Christian (Zeitschrift für Wirtschaftsgeographie, 2015)
The ongoing regional economic change from industry to services employment has long been framed from the perspective of the three-sector model established by Clark, Fisher and Fourastié. While the repeatedly found regularity between service employment and economic growth seems in favour of the model, this paper demonstrates its conceptual and empirical limits. Theoretically, it deploys the approach of the production system to replace an understanding of separate and independent sectors by a perspective of interdependent roles of divided labor. Methodologically, we borrow the distinction of four functional roles - production, circulation, distribution and regulation - and improve existing methodologies to assign these roles to regional economies. We use both models to capture the regional economic change over a period of fifteen years in Southern Germany. Although the evidence seems to confirm the three-sector model, the comparative approach conveys its falsity in understanding economic growth: Regional value creation is not a function of services per se but of the interplay between manufacturing and business services (circulation). The observations that regions with lopsided service growth in distribution fall behind regional growth, and that even rural regions pertaining to strong specializations in manufacturing run ahead of economic growth, are clearly incongruous with the three-sector model. We conclude that the production system concept is a theoretically richer and empirically more valid approach to understand regional development as duality of production and circulation rather than dualism of manufacturing and services.
Online veröffentlicht: 16.01.2016
Gesehen am 08.06.2020
Keywords: Baden-Württemberg